Correlation measurements of individual microwave photons emitted from a symmetric cavity - Bozyigit, D; Lang, C; Steffen, L; Fink, J; Eichler, C; Baur, M; Bianchetti, R; Leek, P; Filipp, S; Wallraff, A (2011)
Superconducting circuits have been successfully established as systems to prepare and investigate microwave light fields at the quantum level. In contrast to optical experiments where light is detected using photon counters, microwaves are usually measured with well developed linear amplifiers. This makes measurements of correlation functions - one of the important tools in optics - harder to achieve because they traditionally rely on photon counters and beam splitters. Here, we demonstrate a system where we can prepare on demand single microwave photons in a cavity and detect them at the two outputs of the cavity using linear amplifiers. Together with efficient data processing, this allows us to measure different observables of the cavity photons, including the first-order correlation function. Using these techniques we demonstrate cooling of a thermal background field in the cavity. © Published under licence by IOP Publishing Ltd.